Balinese Local Wisdom-Based Animation Video to Improve Students’ Cultural Literacy - I Kadek Nandiwardhana; I Gede Astawan; Ketut Herya Darma Utami (Jurnal Media dan Teknologi Pendidikan, 2025)
The low cultural literacy of students is attributed to a lack of understanding of local wisdom in the area, and the learning media used are still not varied. This research aims to develop an animated video media based on Balinese local wisdom to enhance cultural literacy on the topic of Indonesia's cultural diversity for fifth-grade students at SD Negeri 1 Tinggarsari, ensuring a valid, practical, and effective approach. This study employs the ADDIE development model, utilizing data collection methods that include questionnaires and objective tests. Data analysis using qualitative and quantitative methods. The research employs a one-group pre-test post-test design with a sample size of 15 fifth-grade students. The results show that: (1) the research successfully created animated video media based on Balinese local wisdom on the topic of Indonesia's cultural diversity; (2) the product received a validity index of 3.9 with a qualification of very feasible; (3) the practicality of the media was rated very good by students at 94% and 97% by teachers; (4) the t-test results showed a significance value of 0.000 (p < 0.05) indicating that this media is effective in improving students' cultural literacy skills. Thus, this animated video media has been proven valid, practical, and effective in enhancing students' cultural literacy.